Integrating Digital Media and Mind Mapping to Enhance Popular Scientific Writing Skills of Law Students UIN Syarif Hidayatullah Jakarta - Azizah Suryani; Nugraheni Eko Wardani; Kundharu Saddhono (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to analyze and describe improvements in popular science article writing skills through the integration of mind-mapping methods and the use of digital media on news websites among students in the Family Law Study Program at UIN Syarif Hidayatullah Jakarta. This study employs a qualitative descriptive approach with a case study design supported by descriptive quantitative data. The research subjects consisted of 33 students selected through purposive sampling. Data were collected through observation, in-depth interviews, questionnaires, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model across the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques to ensure the credibility of the research findings. The results of the study indicate that the mind mapping method helps students organize their ideas and systematically design a writing framework, thereby reducing barriers to writing. Additionally, digital media serves as a publication platform that requires students to adapt to editorial standards and the revision process. The integration of these two strategies has improved students’ skills in writing popular science articles across cognitive, affective, and practical dimensions and reduced the percentage of students experiencing difficulties from 50% to 26.5%. Thus, this learning model can be applied to college-level writing instruction to enhance students’ digital literacy.